RESEARCH INTO MICROFLORA OF PATIENTS WITH INNOCENT TUMORS OF NASAL CAVITY AND PARANASAL SINUSES - Lutfullayev Umrillo Lutfullaevich; Kobilova Shahodat Shokirovna; Madaminova Nigora Ergashevna; Khalilov Mukhriddin Orifovich; Makhmudova Maftuna Shokirovna (Western European Studies, 2024)
In patients with antritis in innocent tumors of the nasal cavity and paranasal sinuses composition of microflora is different from the primary sinusitis: the extent of the isolation of anaerobes, fungi and microorganisms associations increases with the growth and spread of tumors.
Keywords: innocent tumor; sinusitis